MODELIZATION OF HRM AND PERSPECTIVES FOR THE CAMEROON PUBLIC ADMINISTRATION. - Dr. Aloumedjo Zam Thierry (International Journal of Research Science and Management, 2018)
This paper explores the concept of HRM models as well as its perspectives for African in general and Cameroon in particular. Focusing on the case study of the Cameroon Customs administration. Much has been written about these concepts, but there is no integrated conceptual framework available for the Cameroon contextualization of the said concepts, especially in a public fiscal administration. Our goal here is to develop such a framework. We do this in a number of steps, starting with a presentation of the existing approaches, models, theories with respect to HRM. This is followed by a search for the perspectives in the researcher’s case study, as a starting point for an integrated model and an in-depth case study regarding the Cameroon Customs department. The research methodology used is based on a qualitative approach in order to address efficiently the research problem. I conclude with the presentation of recommendations and suggestions for further research. Analysis of content indicates that if at first sight, it appears that we cannot really talk about a pure HRM model in Cameroon as the HR practices are simply a copy of the US and European systems through concepts such as performance management in addition to the bibliography and teachings in the HR faculties and schools being those authored and produced by western countries. In reality an African and Cameroonian HR model at close sight exists which is a product of a mixed US and European HR policies with contextual adaptations and influences.